The Science and Practice of Lithium Therapy - Malhi, Gin S.; Masson, Marc.; Bellivier, Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a clear and comprehensive guide to the clinical prescription of lithium that draws upon evidence-based knowledge of its mechanisms of action. The book is divided into two parts, on the science of lithium and the practice of lithium therapy. The former covers aspects such as the properties of the lithium ion, pharmacokinetics and pharmacodynamics, impact on neurotransmission, and gene expression modulation. The section on practice includes discussion of variability in response to lithium, use of lithium in the treatment of bipolar disorders, its value in suicide prevention, administration during pregnancy and in the pediatric age group, and side effects. Lithium is arguably the only true mood stabilizer, and its multifaceted effects across many clinical domains have given rise to a resurgence of interest in recent years, fuelled by both researchers and clinicians. Nevertheless, its use remains constrained by exaggerated concerns about potential side-effects. In reality, lithium is a simple molecule that is relatively straightforward to administer and monitor and has potentially profound benefits at a fraction of the cost of contemporary agents. This book dispels the many myths and concerns that surround its use and will be of interest for clinicians and researchers worldwide.
Section I: Science of Lithium: The Ion : Lithium -- Pharmacokinetics and pharmacodynamics of lithium -- Lithium : neurotransmission and cellular mechanisms pathways underlying neuroprogression in bipolar disorder -- Lithium on gene expression modulation -- Neuroimaging and lithium -- Conclusion: overview of potential mechanisms of action of lithium in bipolar disorder -- Section II: Practice of Lithium Therapy -- Introduction of lithium in Medicine and Psychiatry -- Lithium Response variability -- Lithium Response variability: Pharmacogenomics studies -- Lithium Response variability: Biomarkers -- Lithium in acute and maintenance treatment of bipolar disorders -- Lithium and suicide prevention -- Lithium in Bipolar disorders international guidelines -- Lithium and pregnancy -- Lithium in children and adolescents -- Short and mid-term side effects of lithium -- Lithium, kidneys, renal failure -- Lithium intoxication -- Discontinuation and re-use of lithium -- Conclusion : overview of indications and monitoring of lithium in bipolar disorders.
Keywords: Medicine; Neurosciences; Psychopharmacology; Pharmacotherapy; Medicine & Public Health; Psychopharmacology; Pharmacotherapy; Neurosciences